HIV‐1 infection of CD4 T cells impairs antigen‐specific B cell function - Kaw, Sheetal; Ananth, Swetha; Tsopoulidis, Nikolaos; Morath, Katharina; Coban, Bahar M; Hohenberger, Ralph; Bulut, Cem; Klein, Florian; Stolp-Rastätter, Bettina; Fackler, Oliver Till (The EMBO journal, 2020)
Failures to produce neutralizing antibodies upon HIV‐1 infection result in part from B‐cell dysfunction due to unspecific B‐cell activation. How HIV‐1 affects antigen‐specific B‐cell functions remains elusive. Using an adoptive transfer mouse model and ex vivo HIV infection of human tonsil tissue, we found that expression of the HIV‐1 pathogenesis factor NEF in CD4 T cells undermines their helper function and impairs cognate B‐cell functions including mounting of efficient specific IgG responses. NEF interfered with T cell help via a specific protein interaction motif that prevents polarized cytokine secretion at the T‐cell-B‐cell immune synapse. This interference reduced B‐cell activation and proliferation and thus disrupted germinal center formation and affinity maturation. These results identify NEF as a key component for HIV‐mediated dysfunction of antigen‐specific B cells. Therapeutic targeting of the identified molecular surface in NEF will facilitate host control of HIV infection.